Antioxidant Analysis of Different Parts of Several Cultivars of Papaya (Carica Papaya L.). Issue 1 (31st December 2022) - Zhang, Ruining; Lv, Jinhui; Yu, Jing; Xiong, Hailin; Chen, Ping; Cao, Hongxing; John Martin, Jerome Jeyakumar
ABSTRACT: Research and development of natural antioxidants are gaining popularity with their wide application in food and medicine. Papaya ( Carica papaya L.), a plant of medicinal and food value, is widely planted in tropical regions. This study was conducted to compare the tissues of different organs of papaya as well as the leaves and flowers of 9 cultivars of papaya. The three methods, namely, the 2, 2'-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, the 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assay and the ferric reducing antioxidant power (FRAP) assay, were used to determine the total antioxidant activities. Also, the total phenolic content and the total flavonoid content were investigated to evaluate the antioxidant capacity. Our research shows that leaves and roots of papaya manifested higher antioxidant properties among all tested organs, and leaves and flowers of Daqing cultivar exhibited the strongest antioxidant ability. Overall, our results indicate papaya has the potential to become a natural antioxidant resource.